Skin Disease in Livestock and Its Impact on the Tanning Industry: A Comprehensive Review - Putri, N; Pertiwi, V R; Proboningrat, A; Fadholly, A (Politeknik Negeri Lampung, 2026)
Skin diseases in livestock are a significant and often overlooked issue, but they greatly affect the quality of leather, the primary raw material for the tanning industry. Skins affected by diseases such as dermatitis, parasitic infestations, or other skin lesions are prone to defects that lower the economic and aesthetic value of the raw material. This decline in quality directly impacts the productivity and profitability of the tanning industry, as defective hides are of lower grade, reducing yields and limiting the ability to meet domestic and export market standards. This problem also affects livestock farmers through lower skin prices and can weaken added value throughout the supply chain. Our scoping study included papers retrieved from SCOPUS, PubMed, and Web of Science databases, as well as reports from various organizations. This review evaluates multiple types of skin diseases in livestock, the defects they cause, and their implications for leather quality and the broader economy. The findings of this review highlight the importance of multidisciplinary interventions in controlling skin diseases in livestock, thereby improving leather quality and enhancing the sustainability of the tanning industry.